Non-domination and Political Institutions: The Contested Concept of Republican Democracy - Silva,Ricardo (2015)
Following the republican revival of the last few decades, the ideal of freedom as non-domination has become an important point of convergence among republican theorists, especially among those associated with neo-Roman republicanism. Furthermore, all neo-Roman theorists argue that a legitimate republican polity in contemporary societies must take a democratic form to overcome the aristocratic and elitist features pervasive in classical and modern republicanism. This study argues that the emerging concept of republican democracy remains essentially contested despite the increasing agreement on the ideal of liberty being constitutive of the republican tradition. It posits that the meaning of the concept of republican democracy becomes unstable in the transition from the normative ideal to the institutional level of neo-republican reasoning, which is evidenced by the fact that neo-Roman theorists embrace the ideal of non-domination but disagree on the characteristics of the institutional design capable of realizing that ideal. To substantiate this argument, the study compares three recent models of democracy that are somehow associated with neo-Roman republicanism—the electoral-contestatory model, the political constitutionalism model, and the Machiavellian democracy model, championed by Philip Pettit, Richard Bellamy, and John McCormick, respectively.